Spontaneous Fluctuations of Human Pupil Reflect Central Autonomic Rhythms - Calcagnini, G.; Censi, F.; Lino, S.; Cerutti, S. (Methods of Information in Medicine, 2000)
Aim of this study is to assess whether and to what extent LF and HF rhythms contribute to spontaneous pupil diameter fluctuations at rest and during sympathetic activation by Head-Up Tilt Test 70°. ECG, Finapres and Respiration data from 10 normal subjects were recorded simultaneously to spontaneous pupil diameter fluctuations (SPDF). The respiratory rhythm and the LF component were clearly detected in all the SPDF series. The cross-spectrum analysis gave significant results (>0.5) in HF band. During tilt, a reduction in the total variability with a relative increase of the LF component was observed in HR, BP and SPDF signals. The multivariate analysis of the SPDF and of the cardiovascular variability series allows new insights into the physiology of pupil neural control. The effect of tilting on SPDF spectra and the physiological background of the pupil control are consistent with the hypothesis that pupil fluctuations reflect a generalized increase of the sympathetic tone.
Keywords: Pupil Diameter Fluctuations; Autonomic Nervous System; Spectral Analysis